Riddley Walker, Expanded Edition - Hoban, Russell (Book collections on Project MUSE., 1998)
""A hero with Huck Finn's heart and charm, lighting by El Greco and jokes by Punch and Judy ... Riddley Walker is haunting and fiercely imagined and-this matters most-intensely ponderable.""--Benjamin DeMott, The New York Times Book Review""This is what literature is meant to be.""--Anthony Burgess""Russell Hoban has brought off an extraordinary feat of imagination and style ... The conviction and consistency are total. Funny, terrible, haunting and unsettling, this book is a masterpiece.""--Anthony Thwaite, Observer""Extraordinary ... Suffused with melancholy and wonder.